Ontogenetic dynamics of infection with Diphyllobothrium spp. cestodes in sympatric Arctic charr Salvelinus alpinus (L.) and brown trout Salmo trutta L. - Henriksen, Eirik Haugstvedt; Knudsen, Rune; Kristoffersen, Roar; Kuris, Armand M.; Lafferty, Kevin D.; Siwertsson, Anna; Amundsen, Per-Arne (Hydrobiologia, 2015)
Published version available in https://doi.org/10.1007/s10750-015-2589-2 The trophic niches of Arctic charr and brown trout differ when the species occur in sympatry . Their trophically transmitted parasit es are expected to reflect these differences. Here , we investigate how the infections of Diphyllobothrium dendriticum and Diphyllobothrium ditremum differ between charr and trout. These tapeworms use copepods as their first intermediate hos ts and fish can become infected as second intermediate hosts by consuming either infected copepods or infected fish . We examined 767 charr and 368 trout for Diphyllobothrium plerocercoids in a subarctic lake. The prevalence of D. ditremum was higher in charr (61.5 %) than in trout , (39.5 %), but the prevalence of D. dendriticum was higher in trout (31.2 %) than in charr (19.3 %). Diphyllobothrium spp. intensities were elevated in trout compared to charr, particularly for D. dendriticum . Large fish with massive parasite bur dens were responsible for the high Diphyllobothrium spp. loads in trout. We hypothesize that fish prey may be the most important source for the Diphyllobothrium spp. infection s in trout, whereas charr predominantly acquire Diphyllobothrium spp. by feeding on copepods . Our findings support previous suggestions, that the ability to establish in a second piscine host is greater for D. dendriticum than for D. ditremum .